Design of Solar Collector Prototype with Working Fluid Temperature and Pressure Measurement for Energy Harvesting : Rancang Bangun Prototipe Solar Kolektor dengan Pengukuran Temperatur dan Tekanan Fluida Kerja untuk Energy Harvesting - A’rasy Fahruddin; Mochammad Sandi Al Amien; Prantasi Harmi Tjahjanti; Izza Anshory (Academia Open, 2023)
Indonesia is a tropical country, which gets a lot of sunshine every year. Harvesting energy from solar heat is an alternative solution to obtain renewable and environmentally friendly electrical energy. The purpose of this research is to design and test the temperature and flow of the working fluid of a solar collector for energy harvesting. The method used is true experiment research by making a solar collector prototype. Measurement of the temperature and pressure of the working fluid is carried out by varying the power of the heating lamp as a substitute for sunlight in the test. The experimental results show that the greater the heat energy received by the solar collector, the higher the temperature of the working fluid and the resulting pressure during the same test. The highest temperature recorded for the liquid coming out of the solar collector reaches 63.6 oC with a maximum pressure difference of 19.6 Pascals. The results of this test will be followed by testing the flow rate of the working fluid to determine the power potential of the working fluid for harvesting energy. Highlights: Efficiency Enhancement: Optimizing solar collector design for increased heat energy absorption and efficient energy conversion. Temperature-Pressure Correlation: Investigating the relationship between heat energy, working fluid temperature, and pressure for better energy yield. Flow Rate Analysis: Assessing working fluid flow to gauge energy potential and inform effective energy harvesting strategies. Keywords: solar collector, temperature, fluid pressure, energy harvesting